IMPACT OF MUSIC ENGAGEMENT AND VITAL INVOLVEMENT PROGRAMMING ON LOW-INCOME OLDER ADULTS. (16th November 2018) - Chang, L; Kivnick, H; Duncan Davis, L; Montgomery, B; Friedman, J
Abstract: This quasi-experimental study's primary goal was to measure the influence of the AWVIA Program (Art—Wellness--Vital Involvement in Aging), delivered to very low-income older adults living in subsidized senior housing. AWVIA includes Vital Involvement Practice (VIP) plus professionally implemented arts programming. This study delivered a three-month (ten-session) cycle of the Songwriting Works (SW) art modality in ten subsidized senior housing sites where residents had experienced VIP for the previous three years. Experimental sites were matched with controls according to geographic location, resident diversity, and site population size. Control residents did not receive the SW intervention, but did receive ongoing VIP. Quantitative data were collected pre- and post-intervention, to measure Community, Physical Health, Cognition, Emotional, and Fulfillment of Personal Values. Data were analyzed from 276 participants, using repeated-measures ANOVA's. The main independent variable was the experimental (SW + VIP) vs. control (VIP) assignment. Gender and age interaction effects were also explored. Experimental subjects demonstrated statistically significant positive effects in terms of: Community (sense of community; trust in community; reciprocal engagement; perceived social support); Physical Health (self-assessed health and age; chronic pain; exercise); Cognition (word recall); Emotion (emotional well-being; joy of learning and mastery); and Values Fulfillment. These positive findings are particularly striking considering that control subjects were engaged in VISC and may therefore have been expected to score higher on many measures than residents might have, who had not engaged in this component of the intervention. Findings support accumulating evidence that arts activities help promote multi-dimensional well-being among vulnerable elders.